Financial Performance Thorugh Covid 19 Pandemic and Current Stock Valuation of PT Kino Indonesia Tbk - Harijanto, Steven Mikael; Darmansyah, Asep (JURNAL SOCIAL LIBRARY, 2024)
This study examines the financial performance and stock valuation of PT Kino Indonesia Tbk during the COVID-19 pandemic, focusing on evaluating financial health and intrinsic stock value. The research applies financial ratio analysis, Discounted Cash Flow (DCF), and relative valuation methods. Key variables include liquidity, profitability, solvency, and activity ratios, analyzed from financial reports between 2020 and 2023 using a purposive sampling method. The DCF method estimates the intrinsic stock value, while relative valuation compares PT Kino to other companies in the FMCG sector. Results indicate significant financial challenges during the pandemic, particularly in declining profitability ratios, with signs of recovery by 2023. The intrinsic valuation shows the stock may be undervalued in optimistic scenarios, suggesting potential growth. This study offers insights for investors and company management to enhance financial strategies and decision-making in navigating economic disruptions.